EFEKTIVITAS PEMUNGUTAN PAJAK PARKIR DI KOTA SAMARINDA: TINJAUAN DARI PERSPEKTIF HUKUM DAN KEBIJAKAN - Fawwaz Praditya, Fawwaz; Israel, Rehagel; Slamet, Deny (Collegium Studiosum Journal, 2024)
Parking tax is a significant source of Local Revenue (PAD) in Samarinda City, but its implementation faces various challenges. The regulations governing parking tax aim to provide a clear legal framework, yet taxpayer compliance remains low. Weak supervision, limited technology, and low public awareness are the main factors hindering tax collection effectiveness. The use of digital technology in the parking system can enhance taxpayer compliance and reduce revenue leakage. Improving human resource capacity and conducting educational campaigns to raise public awareness are also important. Implementing policies that provide incentives for compliance and strict sanctions for violations is expected to optimize parking tax revenue and improve public services and city infrastructure.